2016
DOI: 10.1021/acs.langmuir.6b02495
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Mechanisms of Reducing Ice Adhesion on Superhydrophobic Surfaces

Abstract: Superhydrophobic (SH) coatings have been shown to reduce freezing and ice nucleation rates, by means of low surface energy chemistry tailored with nano/micro roughness. Durability enhancement of SH surfaces is a crucial issue. Consequently, the present research on reducing ice adhesion is based on radiation-induced radical reaction for covalently bonding SiO2 nanoparticles to polymer coatings to obtain durable roughness. Results indicated that the proposed approach resulted in SH surfaces having high contact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…Rq is commonly used to characterize surface roughness and is an indication of statistical surface height. A higher Rq value means a rougher surface, while a lower Rq value indicates a smoother surface [16,52,53]. As can be noticed Error!…”
Section: Confocal Morphology Analysismentioning
confidence: 82%
“…Rq is commonly used to characterize surface roughness and is an indication of statistical surface height. A higher Rq value means a rougher surface, while a lower Rq value indicates a smoother surface [16,52,53]. As can be noticed Error!…”
Section: Confocal Morphology Analysismentioning
confidence: 82%
“…The resultant situation is that triggering ice nucleation gets more difficulty due to the increasing energy barrier, finally showing a certain extent of icing‐delay performance . Furthermore, the air pockets can be remained after freezing and serve as the original microcracks to reduce the ice adhesion strength, resulting in the adhered ice being extremely easily removed . After a comprehensive insight into these reported literatures, the real anti‐icing potential of hierarchical micro‐nanostructure superhydrophobic surface needs to be further confirmed in the involved application environments due to the obvious distinction (several orders of magnitude) of the volume of reference supercooled droplets.…”
Section: Introductionmentioning
confidence: 94%
“…The more detailed operating procedures are provided in Experimental Section. According to the previous experience and classical wetting theory, the HN‐Surface is expected to entrap more air pockets underneath the droplets and exhibit more robust water repellence than the SN‐Surface . Also, the anti‐icing performance should display the similar situation.…”
Section: Introductionmentioning
confidence: 94%
“…With the development of the material preparation processes, researchers have made material surfaces superhydrophobic by changing the micromorphology of the material surface or coating low-surface-energy materials [20][21][22][23][24][25]. After fabricating the superhydrophobic surfaces with nano/micro-roughness on different substrates, Cohen et al [26] found that superhydrophobic surfaces could significantly reduce the ice adhesion strength. Spitzner et al [27] coated pyroelectric polymer polyvinylidene fluoride on a glass surface to prepare a superhydrophobic film on the substrate surface and found the freezing of water into ice was delayed.…”
Section: Introductionmentioning
confidence: 99%